2018
DOI: 10.1007/s10792-018-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions regarding the use of smart devices for medical photography: results of a patient-based survey

Abstract: Clinical photography in general and, specifically, using smart devices for clinical photographs have gained acceptance among patients. The outcomes of this study may be utilized to create policy guidelines for the use of smart devices as photography tools in the clinics. The findings of this survey can also help to create standardized, uniform patient consent forms for clinical photography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…revealed different results; most patients were comfortable with personal and hospital cameras. [ 17 ] The preference for hospital cameras in the present study and other similar studies may be due to the sense of security between patients. They may think that accessing hospital cameras only during working hours and in the hospital environment will add another level of protection to their digital photos and is considered as a part of data security.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…revealed different results; most patients were comfortable with personal and hospital cameras. [ 17 ] The preference for hospital cameras in the present study and other similar studies may be due to the sense of security between patients. They may think that accessing hospital cameras only during working hours and in the hospital environment will add another level of protection to their digital photos and is considered as a part of data security.…”
Section: Discussionmentioning
confidence: 50%
“…study. [ 17 ] Male patients and those with under diploma educational degrees showed more consent in using the pictures from their lesions. Some female patients need their husband's permission to take photographs.…”
Section: Discussionmentioning
confidence: 99%
“…36 As smartphone usage has become increasingly ubiquitous, more recent studies demonstrate that patients understand the value of clinical photography and are accepting of it using personal devices. 10,37,38 In our study, patients felt most happy consenting to photography for clinical communication (91%) and educational purposes (85%). The patient response to the use of ShareSmart to capture their photographs was favorable (81% preferred ShareSmart as one of their photography modalities or had no preference) and conveyed a sense of security (89%) comparable to a digital camera (83%).…”
Section: Discussionmentioning
confidence: 66%
“…This result supported the findings of previous researchers that, the use of technology in health care is considered to enhance communication and quality of health care. 15,20,21 Hossain et al, 15 reported that majority of patients were aware that smartphones could be used for general health/fitness tracking, obtaining health information, and appointment management similarly, Alameddine et al, 19 concluded that majority of patients (92.6%) recognize the important role of mobile devices in health care delivery and patient care. The result of this study revealed that two third believed that usage of smartphone did not constitute unprofessionalism.…”
Section: Discussionmentioning
confidence: 99%